Loyalitas Konsumen: (Relationship Marketing Herbalife Semarang) - Kuncoro, Amin; Suwarso, Iwan; P, Ratih Hesty; Gunawan, Iwan (Jurnal Bingkai Ekonomi (JBE), 2021)
The purpose of this research is to analyze the relationship between marketing and consumer satisfaction Herbalife in Semarang. The research design used quantitative descriptive using primary data. The research sample is consumers who use products from Herbalife in Semarang who may be 157 respondents. Analysis using multiple partial regression. The results explain that consumers who use Herbalife products in Semarang are loyal because of the emotional closeness factor with fellow users or members. In addition, consumer loyalty increases because of the role of relationships that are strengthened by the benefits of Herbalife products which are indeed beneficial for health.